2020
DOI: 10.1021/acs.jproteome.0c00066
|View full text |Cite
|
Sign up to set email alerts
|

Probing Protein Interaction Networks by Combining MS-Based Proteomics and Structural Data Integration

Abstract: Protein-protein interactions play a major role in the molecular machinery of life and various techniques such as AP-MS are dedicated to their identification. However, those techniques return lists of proteins devoid of organizational structure, not detailing which proteins interact with which others. Proposing a hierarchical view of the interactions between the members of the flat list becomes highly tedious for large datasets when done by hand. To help hierarchize this data, we introduce a new bioinformatics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 87 publications
2
8
0
Order By: Relevance
“…Advantages of our protocol over the other approaches have been recently discussed through two case studies from published AP-MS data ( 16 ). Here we introduce two new case studies showing how Proteo3Dnet can assist users to analyse their data.…”
Section: Use-casesmentioning
confidence: 99%
See 1 more Smart Citation
“…Advantages of our protocol over the other approaches have been recently discussed through two case studies from published AP-MS data ( 16 ). Here we introduce two new case studies showing how Proteo3Dnet can assist users to analyse their data.…”
Section: Use-casesmentioning
confidence: 99%
“…Recently, we have proposed Proteo3Dnet ( 16 ), a new integrative pipeline which stands out from the state of the art mainly by its detection of distant homologies and combination of domain-domain interactions as well as motif-domain contacts. We have shown that our method can identify some direct interaction partners to which proteomics techniques and other algorithms are blind.…”
Section: Introductionmentioning
confidence: 99%
“…Combining proteomics data with 3D searches and comparative modeling has now emerged as a valuable tool to compensate the limitations of most of the above approaches. Servers such as Interactome3D and Proteo3Dnet , allow one to dig efficiently into available 3D structures, gathered in the Protein Data Bank (PDB) to unravel likely physical interactions within a set of proteins. The Complex Portal () is also often used to match the proteins involved in 297 already known mammalian complexes at the structural level.…”
Section: Introductionmentioning
confidence: 99%
“…Combining proteomics data with 3D search and comparative modeling has now emerged as a valuable tool to compensate limitations of each of the above approaches. Servers such as Interactome3D 9 and Proteo3Dnet 10,11 allow one to dig efficiently into available 3D structures, gathered in the Protein Data Bank (PDB 12 ) to unravel likely physical interactions within a set of proteins. The Complex Portal (www.ebi.ac.uk/complexportal/) is also often used to match the proteins involved in 297 already known mammalian complexes at the structural level.…”
Section: Introductionmentioning
confidence: 99%